2020
DOI: 10.1111/iwj.13465
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological profile and antimicrobial resistance among diabetic foot infections in Lebanon

Abstract: Diabetic Foot Infection (DFI) is a challenging complication of diabetes mellitus with a high burden in the Middle East where there is a marked increase in diabetes prevalence and complications. Early detection of DFI and the infectious organisms could result in the early initiation of appropriate antibiotic therapy and improved outcomes. DFI microbiological profiles differ between countries. In our region, Western guidelines are used when initiating treatment for DFI in the absence of local guidance. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 28 publications
7
22
1
1
Order By: Relevance
“…Despite various factors stated to cause delayed wound healing, infections (Fu, 2005) appear to be a principal contributing factor of chronic wound development in the Middle East and Asia particularly in patients with diabetes (Basu et al, 2009;Jiang et al, 2011), leading to disabling diabetic foot ulcers (Sugandhi and Prasanth, 2014;Tekin et al, 2014;Li et al, 2018;Jouhar et al, 2020;Guan et al, 2021). The greatly diverse and exceptionally dynamic genetic composition of the successful opportunistic pathogens primarily contributes virulence and antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Despite various factors stated to cause delayed wound healing, infections (Fu, 2005) appear to be a principal contributing factor of chronic wound development in the Middle East and Asia particularly in patients with diabetes (Basu et al, 2009;Jiang et al, 2011), leading to disabling diabetic foot ulcers (Sugandhi and Prasanth, 2014;Tekin et al, 2014;Li et al, 2018;Jouhar et al, 2020;Guan et al, 2021). The greatly diverse and exceptionally dynamic genetic composition of the successful opportunistic pathogens primarily contributes virulence and antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, in their study they considered only E. coli and Klebsiella pneumoniae in the analysis of ESBL producing bacteria, while we documented all enterobacteriaceae producing ESBL. More recent studies demonstrated higher rates of ESBL, such as the study by Jouhar et al which found an ESBL prevalence of 25% among 314 enterobacteriaceae isolates (Jouhar et al, 2020). Some studies focusing specifically on E. coli found even higher rates of ESBL, ranging from 43.7% to 77.8% (Al-Joufi et al, 2020;Li et al, 2018;Najari et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…An organism’s level of microbiota as well as its ability to interact with other microorganisms are important considerations. When the number of bacteria per gram of tissue surpasses 105, the condition is referred to as an infection [ 36 ]. It is possible for skin commensal bacteria to colonize the wound left behind by DFUs, even when the wound is not infected since the host’s immune system has not yet been activated [ 36 ].…”
Section: Infection Of Dfusmentioning
confidence: 99%
“…When the number of bacteria per gram of tissue surpasses 105, the condition is referred to as an infection [ 36 ]. It is possible for skin commensal bacteria to colonize the wound left behind by DFUs, even when the wound is not infected since the host’s immune system has not yet been activated [ 36 ]. Triggers might be physical, chemical, or mechanical in nature.…”
Section: Infection Of Dfusmentioning
confidence: 99%
See 1 more Smart Citation